Guide :

# Can i get that answer? 8+3x = -7

8+3x= 7      this ecuation

## Research, Knowledge and Information :

### 3x+7=8 - Math homework help - HomeworkMarket.com

Is that your homework? Bulls eye!!! ... Normally we charge \$1.00 for this answer Today, you can get it FOR FREE if you ... 3x+7=8. 3x+7=8.

### How do you solve -3x+1= 5x-7? | Socratic

... (blue)(step 1):- 1=5x+3x-7 color(blue)(step 2:- 1+7=5x+3x color(blue)(step 3:- 8=8x color(blue)(step 4:- x ... You can reuse this answer Creative Commons ...

### Checking Answers Using Algebra Calculator - MathPapa

Checking Answers Using Algebra Calculator. ... Example Answer x=6 ... For system of equations x+y=8 and y=x+2, check ...

### How can x+8=-x+7 be set up as a system of equatio... - OpenStudy

How can x+8=-x+7 be set up as a system of equations A. Y=x+8 Y=-x+7 B. y=x+8 Y=-3x+7 C. Y=x+5 Y=-2x+11 D. Y=8 Y=-3x+7This equation ... Get our expert's. answer on ...

### 3x-7=1-x - Algebra homework help

You can ask homework questions and get assistance. ... Normally we charge \$1.00 for this answer Today, you can get it FOR FREE if you ... (8 words) 3x-7=1-x 3x+x-7=1 ...

### How do you solve 2x-y=7 and 3x+y=8? | Socratic

Substitute this expression for y in the second equation and get 3x + (2x-7) = 8 5x-7=8 5x ... How do you solve #2x-y=7# and #3x+y=8#? ... Start with a one sentence ...

### What is the solution to the compound inequality 5x + 7 > −8 ...

What is the solution to the compound inequality 5x + 7 > −8 and 3x + 7 ≤ 19? - 2064399. 1. ... Not sure about the answer?

### Which best describes the solution set for the inequality ...

Which best describes the solution set for the inequality below? 3x + 7 ≤ 4x – 8 or –2x + 3 ≥ 1 - 2939643 ... Answer quality is ensured by our experts.

### Can You Solve: 7(5y-2)>6(6y-1) -3x+8 | Chegg.com

Answer to Can you solve: 7(5y-2)>6(6y-1) -3x+8... Textbook Solutions Expert Q&A ... Get this answer with Chegg Study View this answer. OR.

### solve for X, show work 5x + 7 + 3x = -8 + 3x - OpenStudy

solve for X, show work 5x + 7 + 3x = -8 + 3xadd the x's on either side of the equation and tell me what you get. ... We 've verified this expert answer for you, ...

## Suggested Questions And Answer :

### times student will get 3 out of 10 questions right randomly guessing 4 choice questions

This is a binomial distribution, where p=1/4=0.25, the chance of getting the correct answer, and 1-p=0.75, the chance of getting the wrong answer. The distribution's last 4 terms are: (1-p)^10, 10(1-p)^9p, 45(1-p)^8p^2, 120(1-p)^7p ^3. These represent the chances of 0, 1, 2, 3 correct answers in 10. The coefficients are the number of ways of 0, 1, 2, 3 correct answers can be mixed with wrong answers. We need the last in this list which evaluates to 120*0.75^7*0.25^3=0.25 approx. and is the probability of getting exactly 3 right out of 10.

### In a mathematics emathematics, each correct answergets 2 marks and a wrong answer attract -1, ola got a total of 19 in aquiz with 20 questions. How many correct answers did he get?

If we call the number of right answers R and the number of wrong answers W, 2R-W=19. Also we know W+R=20. Add the two equations: 3R=39 so R=13, 13 correct answers. 13 correct answers gains 26 points; 7 incorrect answers loses 7 points and 26-7=19.

### The first die is 3 or the sum is 8

The answer posted above is correct. However the same answer can be arrived at in another way also. Tho get a total of 8 for 2 dies none of the dice must have a '1'. The probability that the first dice will not have a '1', or that it will have 2, 3, 4, 5, or 6, are: Probability of first dice not getting 1 = 5/6 This is because the probability of getting any number from 1 to 6 are equal. For each occurrence of the number 2 to 6 for dice the second dice must get a number given by: Required number if dice 2 = 8 - n Where: n = number of dice 1 As the probability of getting any one number is equal to 1/6, the probability that the second dice will have exactly the required number is: Probability of second dice getting the number (8 - n) = 1/6 The probability of getting sum of 8: Probability that sum is 8 = (Probability of first dice not getting 1)*(Probability of second dice getting the number (8 - n)) = (5/6)*(1/6) = 5/36 Answer: Probability of sum of two dice as 8 = 5/36

### Divide 2x4 - 5x3 - 8x2 - 17x - 4 by x + 4

I'm assuming the question reads: divide 2x^4-5x^3-8x^2-17x-4 by x+4, where the caret (^) means "to the power of". Long division in algebra is similar to long division in arithmetic. We lay out the dividend, which is the long expression, as we would lay out a number we're going to divide into. To the left of it we write the divisor, which is x+4. How many x's go into 2x^4? The answer is 2x^3 because 2x^3*x=2x^4. OK, the first term in the quotient (the answer) is 2x^3. We multiply x+4 by 2x^3, which gives us 2x^4+8x^3, and we write this under the dividend so that the powers of x line up. We should have 2x^4 under 2x^4 in the long expression and 8x^3 under 5x^3 in the long expression. We now have to work out 2x^4-5x^3-(2x^4+8x^3). Always beware of the + and - signs, it's so easy to make a mistake. The subtraction gives us -13x^3. We now look at this result and the next term in the long expression which is -8x^2. How many times does x go into -13x^3? The answer is -13x^2 times. That's the next term in the quotient following 2x^3. Multiply x+4 by -13x^2 and we get -13x^3-52x^2, subtract this from -13x^3-8x^2 and we get 44x^2. We continue the process bringing in successive terms from the dividend until we get to the end, when we'll perhaps be left with a remainder. The answer is the quotient=2x^3-13x^2+44x-193 remainder 768. Is that the answer you get?

### what is the answer to 18-4t/0.5=20 ?

Perhaps it was the fraction that put you off, or was it the decimal in the denominator. I guess you want to find the value of t. Let's get rid of the fraction by multiplying both sides of the equation by 0.5. It's not clear in the question whether the problem is 18-(4t/0.5)=20 or (18-4t)/0.5=20. The brackets tell us what has to be worked out first. I'm going to provide solutions whichever one of these is the problem. First, 18-(4t/0.5)=20 Multiplying both sides by 0.5 we get 18*0.5-4t=20*0.5 giving us 9-4t=10. The decimals have been swallowed up in the multiplication. 0.5 is the same as 1/2, but if you didn't know that, multiply by 5 and move the decimal point back one place. So, for example, 5*18=90. The decimal point invisibly sits after 90, so moving it back a place makes it 9.0 which is just 9. So 9-4t=10. We need to get the numbers on one side of the equation and the unknown on the other side. At this stage we don't want to separate 4 from 4t. OK, let's keep the unknown on the left, so we get -4t=10-9, giving us -4t=1. When we move things from one side of an equation to the other plus becomes minus, and minus becomes plus, multiply becomes divide, and divide becomes multiply. So this is the same as 4t=-1, and t=-1/4. Second, (18-4t)/0.5=20 Multiply both sides by 0.5 and we get 18-4t=20*0.5, in other words 18-4t=10. Let's separate the unknown from the numbers, but this time we'll take the unknown over to the right (it doesn't matter which side really). So we get 18-10=4t. Therefore 8=4t, the same as 4t=8, so t=2. That looks like the simpler of the two answers, so my guess is that it's what the question really was, don't you think? It's important that questions are written correctly because, as you can see, we came up with two quite different answers.

### 8/9 - 1/5=

8/9 - 1/5= how do i get the answer please explain dont just give answer please thanks When adding or subtracting fractions, you must always use a common denominator. The easiest way to determine that denominator is simply to multiply them: 9 * 5 = 45. Multiply each fraction by a fraction that is equivalent to 1, but will result in the same denominator. For this problem, multiply the first fraction by 5/5, and multiply the second fraction by 9/9. Both 5/5 and 9/9 are equal to 1, so you are NOT changing the VALUE of the fractions, merely their representation. (8/9) * (5/5) - (1/5) * (9/9) When multiplying fractions, multiply the numerators to get the new numerator, and multiply the denominators to get the new denominator. (8/9) * (5/5) - (1/5) * (9/9) (8 * 5) / (9 * 5)  -  (1 * 9) / (5 * 9) 40/45 - 9/45 Now, simply subtract. 40/45 - 9/45 31/45